Model Studies of Metallurgical Processes Based on the Example of Blowing Steel with Argon - T. Merder; J. Pieprzyca; R. Wende; J. Witek; M. Saternus (Archives of Foundry Engineering)
The task facing steel producers, which is to limit the negative impact of their production on the environment, necessitates changing the technologies used so far. These changes often require knowledge of the mechanisms of physical phenomena, mainly hydromechanical ones, occurring in steel reactors. Identification of these mechanisms in industrial conditions is difficult and often impossible for fundamental reasons. A frequently used research tool in such cases are water physical models of metallurgical reactors used in steel production. Such models are built in accordance with the principles of similarity and fluid mechanics. The article presents an overview of achievements in the field of physical modelling of steelmaking processes (including blowing liquid steel with inert gases), mathematical principles constituting the basis for the construction of steelmaking reactor models and the latest trends in their application. As an example, the results of model tests on the possibility of using a new solution in the construction of a slot-type gas-permeable module (KS diffuser) in the process of blowing liquid steel with inert gases in a steel ladle are presented. The tested process is aimed at preparing liquid steel for casting and largely determines the quality of the semi-finished product, which is a steel ingot.